Angola Economic Update, June 2014 - World Bank (Washington, DC, 2014)
Angola's economy decelerated in 2013 due to the weak performance of the oil sector but the non-oil economy expanded rapidly. Similarly, lower oil related export earnings and higher imports narrowed the current account surplus. Enhancing export competitiveness and implementing tax related reforms will reduce the co-movement between the current account and the fiscal account balances. Expanded agricultural output and lower food import prices helped curb the inflation rate to a single digit. While the non-oil economy expands, maintaining the observed level of international reserves will help shield the country from potential oil price fluctuations. This economic update analyzes recent economic developments in Angola and situates them in a medium-term global context. It evaluates the implications of macroeconomic trends and policy reforms in terms of the government's stated development objectives.